Pengaruh Media Sosial dan Partisipasi Masyarakat Terhadap Minat Berkunjung Wisatawan ke Mangrove Tanjung Batu Sekotong - Baiq Rini Hendriani; Handry Sudiartha Athar (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2026)
This study aims to determine the influence of social media and community participation on tourist interest in visiting the Tanjung Batu Sekotong Mangrove tourist destination. The background of this study stems from the importance of effective tourism promotion and the active role of local communities in destination management to attract tourists. The research method used was quantitative with an associative approach. The study population included prospective tourists who were aware of or had seen the Tanjung Batu Sekotong Mangrove tourism promotion. A sample of 60 respondents was selected using a purposive sampling technique, and data were collected through a questionnaire. Data analysis was performed using multiple linear regression with the help of SPSS. The results showed that social media had a positive and significant effect on tourist interest in visiting, meaning that the more intense and effective the promotion through social media, the higher the tourist interest in visiting. Community participation also had a positive and significant effect on tourist interest, indicating that active community involvement in destination promotion and management enhances tourist attractiveness. Simultaneously, these two variables contributed significantly to increasing tourist interest in visiting. These findings confirm that the combination of optimal digital promotion and local community empowerment is an effective strategy for sustainable tourism development.